2011
DOI: 10.1002/ajh.22203
|View full text |Cite
|
Sign up to set email alerts
|

Non‐transferrin bound iron in Thalassemia: Differential detection of redox active forms in children and older patients

Abstract: Non-transferrin bound iron (NTBI) is commonly detected in patients with systemic iron overload whose serum iron-binding capacity has been surpassed. It has been perceived as an indicator of iron overload, impending organ damage and a chelation target in poly-transfused thalassemia patients. However, NTBI is a heterogeneous entity comprising various iron complexes, including a significant redox-active and readily chelatable fraction, which we have designated as ''labile plasma iron'' (LPI). We found that LPI le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 33 publications
(90 reference statements)
0
42
0
Order By: Relevance
“…17,18 The assay is based on the binding of NTBI in serum to fluorescein-DFO (Fl-DFO), causing quenching of its fluorescence. Briefly, each serum sample is measured under two separate conditions: A, with Fl-DFO only; and B, as in condition A but in the presence of a large excess of non-fluorescent DFO.…”
Section: Measurement Of DCI (Directly Chelatable Iron) In Serum Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…17,18 The assay is based on the binding of NTBI in serum to fluorescein-DFO (Fl-DFO), causing quenching of its fluorescence. Briefly, each serum sample is measured under two separate conditions: A, with Fl-DFO only; and B, as in condition A but in the presence of a large excess of non-fluorescent DFO.…”
Section: Measurement Of DCI (Directly Chelatable Iron) In Serum Samplesmentioning
confidence: 99%
“…The fact that inclusion of nitrilotriacetic acid in the DCI assay did not reveal additional DFO chelatable material was taken as an indication that the DCI values represented most of the NTBI fraction. 18 …”
Section: Measurement Of DCI (Directly Chelatable Iron) In Serum Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Plasma NTBI apparently comprises several subspecies, which may be classified by their chemical composition, chemical reactivity or susceptibility to chelation. [6][7][8][9][10][11][12][13][14][15] The chemical composition of NTBI is heterogeneous and it is thought that there are several circulating isoforms, that is Fe(III) bound to albumin and citrate and potentially to acetate, malate and phosphate. [6][7][8]14 Of these, citrate has the highest affinity for Fe(III), and under physiological conditions two isoforms dominate, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…5,13,24 Due to the complexity and potential clinical importance of NTBI, several assays have been developed for its detection. 6,[10][11][12]15,[25][26][27][28][29] In our previous round robin 1 we found that NTBI values of patients with HFE-related hemochromatosis differed considerably depending on which of various assays was used. 30 We concluded that NTBI assays were insufficiently standardized and the most pertinent assay for clinical applications was uncertain.…”
Section: Introductionmentioning
confidence: 99%